Determination of 35 Free Amino Acids in Tea Using Ultra-Performance Liquid Chromatography Coupled With Quadrupole Time-of-Flight Mass Spectrometry - Li, Jian; Ma, Junmei; Li, Qiang; Fan, Sufang; Fan, Lixin; Ma, Hongyu; Zhang, Yan; Zheng, Lei (Frontiers in Nutrition, 2021)
A ultra performance liquid chromatography coupled with quadrupole-time of flight mass spectrometry (UPLC-Q-TOF/MS) method was used to simultaneously detect the 35 free amino acids. Tea samples were extracted with boiling water bath, then separated by XBridge BEH Amide column by gradient elution. The exact mass and MS/MS spectra of the target compound was detected under the TOF-MS and IDA-MS/MS mode. The results showed that mass accuracy error of 35 free amino acids were lower than 5.0×10-6, good linear relationships in the range of 0.5-1000 ng/mL, and the correlation coefficient was greater than 0.998 0. The limits of detection were in the range of 0.13-25.00 mg/kg and the limits of quantitation were in the range of 0.25-50.00 mg/kg. Recoveries of the method were in range of 70.1%-105.1%, and the relative standard deviations were in range of 0.45%-11.0%(n=6). The method is sensitive and accurate, and is suitable for the rapid determination of free amino acids in the analysis of tea quality.